Research of the effect of temporary reservation on the reliability of equipment locomotives (Transport systems and technologies, 2019)
The article deals with the issues of the effect of the temporary reservation of the work of a separate locomotive equipment on its reliability, under the conditions different laws of distribution of time of work, time of recovery, time for temporary reservation. At the same time, the issue of the influence of the random nature of the occurrence of refusals with the justification of the strategy of their prevention is considered. The effect of temporary reservation of work of separate equipment of locomotives on its reliability is investigated. Calculation takes place taking into account different laws of distribution of time of work to the failure, time on recovery, time on temporary reservation.This research is relevant because, in recent years, in our country gradually develops high-speed railway traffic. In the majority, the high-speed rolling stock (SRS) operating in the country, built abroad, and not always the mode of its operational loads meets the recommendations of suppliers of this technique. This leads to a breakdown in train traffic and great downtime, due to both the general condition of the railways and the intensity of the use of this SRS.One more negative factor is the problem of organization of technical maintenance (TM) and current repair (СR) of this rolling stock. But not only for SRS there are such problems, because the current traction rolling stock has reached or exceeded the normative term of use, the repair base is updated slowly, technological processes TM and СR are not corrected during the life cycle. All this requires both practical and theoretical substantiation of the strategy and tactics of TM and СR of the transport rolling stock.Therefore, there were formulated and scientifically substantiated methods for ensuring and improving the reliability of technique, on the basis of the analyzed functional relationships between the reliability indicators and the calculated ratios for reliability indicators of complex systems, which are is the traction rolling stock and locomotives.It has been determined that the temporary reservation of the work of the locomotive systems significantly affects the time to the failure, recovery time and readiness factor and significantly improves these parameters, in contrast to the system performance without temporary reservation. It is also concluded that it is advisable to organize the recovery process in such a way that the distributions of time for recovery were close to gamma-distribution. And the value of the readiness factor depends significantly on the type of the law of distribution of exploitation to failure and the type of the law of distribution of time for recovery.
Keywords: random distribution law, reservation, availability, average time, average recovery time